The assessing factors of trust in zakah governance among income zakah payers: A case study in Kelantan. - Mohd Zaki, Adeeba Najihah; Ab Rahman , Siti Maziah; Shaari, Rustam (Journal of Islamic, Social, Economics and Development, 2025)
Despite the vital role that zakah plays in fostering social welfare and economic fairness within Muslim communities, there is a major lack of confidence between zakah payers and zakah organizations, notably in Malaysia. This skepticism is frequently linked to perceived shortcomings in governance procedures, such as insufficient fairness, quality of services, accountability and transparency in the management and governance of zakah. Previous research has found that these reasons contribute to individuals' reluctance to fulfill their zakah obligations through formal channels, resulting in a drop in zakah compliance and compromising the effectiveness of zakah distribution systems. Furthermore, the Council of Islamic Religion and Malay Customs of Kelantan (MAIK) confronts hurdles in terms of public perception of governance quality, exacerbating trust issues. The lack of defined principles and standards for zakah governance has led in discrepancies in operational processes and a scarcity of credible information about fund management. As a result, understanding the causes of trust in zakah governance is critical for increasing MAIK's legitimacy and effectiveness. As a result, additional empirical research is needed to uncover the elements influencing trust in Zakah governance, particularly in Kelantan. This quantitative study examines the drivers of trust in zakah governance, with a focus on MAIK, using Social Trust Theory. The study attempts to discover crucial elements that influence zakah payers' faith in zakah authorities, which is critical for increasing compliance and boosting the effectiveness of zakah distribution. A standardized survey was used to collect data from zakah payers of various demographics to investigate their attitudes of accountability, transparency, fairness, and service quality within MAIK. The findings show that accountability, as expressed in the credibility and competency of zakah authorities, has a considerable impact on payer trust. Furthermore, transparency in financial reports and operational operations is critical to instilling trust in the institution. The report also emphasizes the necessity of fairness in both collecting and distribution processes, which helps to foster a positive impression of zakah governance. Using Social Trust Theory, this study demonstrates that trust is a communal expectation molded by institutional behavior and governance quality. These findings imply that increasing trust through better governance practices can lead to enhanced zakah compliance, benefiting social welfare and economic fairness in the community. This study provides a basic framework for the future research on trust dynamics in zakah governance, as well as practical recommendations for policymakers looking to strengthen zakah governance systems. Finally, this study can suggest a strategic strategy for optimizing the improvement of zakah collection in Kelantan.